2002
DOI: 10.1083/jcb.200205098
|View full text |Cite
|
Sign up to set email alerts
|

Neural cell adhesion molecule promotes accumulation of TGN organelles at sites of neuron-to-neuron contacts

Abstract: Transformation of a contact between axon and dendrite into a synapse is accompanied by accumulation of the synaptic machinery at this site, being delivered in intracellular organelles mainly of TGN origin. Here, we report that in cultured hippocampal neurons, TGN organelles are linked via spectrin to clusters of the neural cell adhesion molecule (NCAM) in the plasma membrane. These complexes are translocated along neurites and trapped at sites of initial neurite-to-neurite contacts within several minutes after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
133
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(138 citation statements)
references
References 62 publications
(120 reference statements)
4
133
0
Order By: Relevance
“…The importance of the Golgi structure necessary for the high turnover of dendritic membrane surface is reflected by the presence of so-called dendritic outposts in the main dendrites (Sytnyk et al, 2002;Horton and Ehlers, 2003). In our hippocampal cultures, Golgi-targeted PKD reporter revealed high endogenous PKD activity at the neuronal Golgi complex.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The importance of the Golgi structure necessary for the high turnover of dendritic membrane surface is reflected by the presence of so-called dendritic outposts in the main dendrites (Sytnyk et al, 2002;Horton and Ehlers, 2003). In our hippocampal cultures, Golgi-targeted PKD reporter revealed high endogenous PKD activity at the neuronal Golgi complex.…”
Section: Discussionmentioning
confidence: 90%
“…A thread-like and reticular structure of the Golgi apparatus has been already described in many neuronal types (Takamine et al, 2000;Fujita and Okamoto, 2005;Horton et al, 2005). Central neuronal Golgi complex is localized in the soma and often extends into the principal dendrites, but Golgi elements were also found as discontinuous structures in the distal dendrites, often near synaptic contacts or in dendritic spines (Gardiol et al, 1999;Pierce et al, 2001;Sytnyk et al, 2002;Horton and Ehlers, 2003). The dispersed localization of the Golgi apparatus indicates unique spatial regulation of the neuronal secretory pathway compared with other mammalian cells.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, postsynaptic expression of another L1-family member, neurofascin, may be necessary for the establishment of basket cell axon terminal synapses on cerebellar Purkinje cells (Ango et al, 2004); also another family member is found in dendrites of developing cortical neurons and modulates neuronal positioning and dendrite orientation (Demyanenko et al, 2004). Indeed, members of a closely related family of cell adhesion molecules, the NCAMs, associate with both the presynaptic and postsynaptic sides of early synaptic contacts and may play a major role in synaptogenesis and synapse maturation (Sytnyk et al, 2002;Polo-Parada et al, 2004). In fact, NCAM180 associates with NR2A-containing NMDA receptors in the central region of the postsynaptic membrane in hippocampus; this distribution changes following induction of long-term potentiation in vivo in adult rodents (Fux et al, 2003) where NCAMs help mediate synaptic plasticity (Bukalo et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Long lasting stability of synapses (months or years), however, suggests that synaptic pools of cell adhesion molecules (protein life time hours or days) have to be also homeostatically and continuously replenished over prolonged periods of time without compromising synapse stability and composition. Mechanisms of such replenishment remain poorly understood.Among synaptic adhesion molecules, the neural cell adhesion molecule (NCAM), 2 a member of the immunoglobulin superfamily of adhesion molecules, was shown to be involved in mechanical stabilization of interneuronal contacts and their transformation into synapses (12,14). In mice, deficiency in NCAM results in impaired long term potentiation, increased aggression and anxiety, deficits in spatial learning, and exploratory behavior (15-21).…”
mentioning
confidence: 99%